THE USAGE OF RELATIVE PRONOUNS IN COMPLEX SENTENCES IN UZBEK AND ENGLISH LANGUAGES - Nematov Bahodir Mamasharifovich (International Engineering Journal For Research & Development, 2022)
Relative pronouns are used in complex sentences. They are part of the clause which follows a noun or noun group and make the clause dependent. Clauses which begin with relative pronouns are sometimes called relative clauses or adjectival clauses. Use a relative clause to give more information about a noun or pronoun. A relative pronoun is a pronoun that relates to the word that it modifies and is not specific. In English, relative pronouns are who, whom, which, whose, and that. A relative pronoun links two clauses into a single complex clause. It is similar in function to a subordinating conjunction. Unlike a conjunction, however, a relative pronoun stands in place of a noun. A complex sentence based on the subordinate-dominant relation of more than one simple sentence, that is, following one after the other, is called a complex sentence: e.g. When the root nourishes, the branches sprout.